(untitled) (Revista Venezolana de Salud Pública, 2018)
The Sustainable Development Goals (SDGs) represent a group of goals that make up a plan agreed by all the countries of the world with the aim of improving the quality of life of millions of people who inhabit our planet. The second of these objectives, which is framed within the United Nations Development Program (UNDP), is "to end hunger, achieve food security and improve nutrition and promote sustainable agriculture" or also known as "HUNGER ZERO." More than 1,000 million people subsist on less than a dollar a day and approximately 795 million people suffer from chronic malnutrition worldwide, with the child population being the most severely affected.